Early diagnostic indicators of childhood apraxia of speech in young children with 7q11.23 duplication syndrome: preliminary findings. - Abbiati, Claudia I.; Velleman, Shelley L.; Overby, Megan S.; Becerra, Angela M.; Mervis, Carolyn B. (Clinical Linguistics & Phonetics, 2023)
Limited evidence for early indicators of childhood apraxia of speech (CAS) precludes reliable diagnosis before 36 months, although a few prior studies have identified several potential early indicators. We examined these possible early indicators in 10 toddlers aged 14–24 months at risk for CAS due to a genetic condition: 7q11.23 duplication syndrome (Dup7). Phon Vocalisation analyses were conducted on phonetic transcriptions of each child's vocalisations during an audio-video recorded 30-minute play session with a caregiver and/or a trained research assistant. The resulting data were compared to data previously collected by Overby from similar-aged toddlers developing typically (TD), later diagnosed with CAS (LCAS), or later diagnosed with another speech sound disorder (LSSD). The Dup7 group did not differ significantly from the LCAS group on any measure. In contrast, the Dup7 group evidenced significant delays relative to the LSSD group on canonical babble frequency, volubility, consonant place diversity, and consonant manner diversity and relative to the TD group not only on these measures but also on canonical babble ratio, consonant diversity, and vocalisation structure diversity. Toddlers with Dup7 also demonstrated expressive vocabulary delay as measured by both number of word types orally produced during the play sessions and primary caregivers' responses on a standardised parent-report measure of early expressive vocabulary. Examining babble, phonetic, and phonotactic characteristics from the productions of young children may allow for earlier identification of CAS and a better understanding of the nature of CAS.